Legal Regulation of Joint Protection of State Border by Border Guard Units of Ukraine and Hungary - Liashuk, Roman; Kupriyenko, Dmytro (Magyar Rendészet, 2016)
Unilateral protection of border is costly and insufficiently effective. Therefore, counteraction to numerous cross-border threats will be provided in case of the joint protection of the Ukrainian-Hungarian border by border guard divisions of the State Border Guard Service of Ukraine and units of Border Police of Hungary. Their cooperation is performed in forms of investigation of violations of the border regime, interaction during control of the border crossing, joint patrolling and exchange of information. In order to achieve the goal of the joint protection of the state border of Ukraine and Hungary, it is necessary to implement an effective scientifically grounded system of counteraction to cross-border threats which would be adequate, foreseeing and flexibly reacting to changes of the situation.